Method for preparing graphite from peat and graphite

By graphitizing the screened peat at a high temperature of 2500-2900℃, high-quality scale graphite is produced, which solves the problem that peat is difficult to graphitize, and achieves efficient and energy-saving graphite production, further improving the high added value of peat resources.

CN119591099APending Publication Date: 2025-03-11ZAOZHUANG SANXING ADVANCED MATERIALS +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411768743.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, since peat is aware that the optical isotropic structure is difficult to graphitize, it is difficult to think of graphitizing peat into graphite to further increase the high added value of peat resources.

Method used

High-quality scale graphite was prepared by screening peat and graphitizing at a high temperature of 2500-2900°C. The method includes drying, heating procedures and appropriate graphitization time to ensure high graphitization degree and complete lattice development.

Benefits of technology

It has achieved significant reduction in energy consumption costs for graphite production, energy conservation and emission reduction, and maximized the high added value of peat resources, overcoming the bias of the existing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591099A_ABST
    Figure CN119591099A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of high value-added utilization of peat resources and artificial graphite, and particularly relates to a method for preparing graphite from peat and graphite. The method comprises the following steps: screening peat; and graphitizing the screened peat to obtain crystalline flake graphite. According to the method, high-quality graphite is generated from peat, so that preparation of graphite by peat graphitization becomes possible, the prejudice of the prior art is overcome, the energy consumption cost of graphitization processing enterprises can be remarkably reduced, energy conservation and emission reduction are facilitated, and high value-added utilization of peat resources is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high value-added utilization of peat resources and artificial graphite, and specifically relates to a method for preparing graphite from peat and the graphite. Background Art

[0002] Graphite is a layered mineral with excellent electrical, thermal and mechanical properties. It is widely used in metallurgy, casting, machinery, electrical, nuclear energy, national defense and other industries. Graphite is also a raw material for preparing high value-added carbon materials, such as high-purity ultrafine graphite, flexible graphite, graphite intercalation compounds, lithium-ion battery negative electrodes, and new carbon materials such as fullerene, graphene, carbon quantum dots, etc. Graphite can be divided into natural graphite and artificial graphite, of which natural graphite is a non-renewable resource.

[0003] Artificial graphite is synthesized by high-temperature (2500-3000℃) graphitization using high-quality petroleum coke or coal-based needle coke as raw materials. This method is already very mature, and the finished products produced are widely used in metallurgical electrodes and power batteries. However, this technical route faces two major problems. First, the raw materials are uncontrollable, the import price fluctuates violently, and it is heavily dependent on oil resources; second, the energy consumption is high. The temperature required for artificial graphite is as high as 3000℃, and the power consumption during the production process is extremely high.

[0004] The main use of peat is to burn it as an energy mineral resource, and the slightly higher added value is to use it as green waste to improve soil. Peat is an organic mineral resource formed by the transformation and accumulation of dead plant residues in swamps. It is a precursor to coal that has not yet undergone gelation. In its natural state, peat is composed of three phases: liquid, gas and solid. The solid phase mainly contains organic matter and a large amount of minerals. The minerals in it cause a large amount of fly ash and slag to be produced during the combustion of peat, and its heat is low, far inferior to coal. Therefore, the current added value of the entire peat resource is low. Exploring the high added value utilization of peat resources has important scientific and practical significance.

[0005] Peat is an unformed "quasi-young coal" that has not undergone diagenesis in the coal chemistry sense. The number of aromatic nuclear rings in the basic structural unit is 1-3. It has an optically isotropic structure that is difficult to graphitize and is an excellent raw material for preparing activated carbon.

[0006] In summary, at present, due to the widespread recognition that peat has an optically isotropic structure that is difficult to graphitize, those skilled in the art usually do not think of graphitizing peat to prepare graphite to further increase the high added value of peat resources, and there are no related reports in the prior art.

[0007] Accordingly, this field requires a new technical solution to solve the above technical problems. Summary of the invention

[0008] The present invention aims to solve the above technical problems, namely, to solve the problem in the prior art that it is difficult to think of graphitizing peat to prepare graphite to further increase the high added value of peat resources due to the general perception that peat has an optically isotropic structure that is difficult to graphitize. The present invention explores the feasibility of peat graphitization, and uses peat to generate high-quality graphite, which can significantly reduce the energy cost of graphitization processing enterprises, contribute to energy conservation and emission reduction, and realize high added value utilization of peat resources, thus overcoming the prejudice of the prior art.

[0009] In a first aspect, the present application provides a method for preparing graphite from peat, comprising:

[0010] sifting peat;

[0011] The selected peat is graphitized to obtain the product.

[0012] In the preferred technical solution of the above method for preparing graphite from peat, the graphitization temperature is 2500-2900°C.

[0013] In the preferred technical solution of the above method for preparing graphite from peat, the graphitization time is 2.5 to 3.5 hours.

[0014] In a more preferred technical solution of the above method for preparing graphite from peat, the graphitization time is 3 hours.

[0015] In the preferred technical solution of the above method for preparing graphite from peat, the quartz content in the screened peat is 35-60%.

[0016] In the preferred technical solution of the method for preparing graphite from peat, the following heating procedure is set during the graphitization:

[0017] Raise the graphitization temperature to 2500-2900°C and graphitize for 2.5-3.5 hours;

[0018] As a preferred heating procedure, it is as follows:

[0019] The first stage: rise to 1000-1400℃ and maintain for 0.5-1.5 minutes;

[0020] The second stage: rising to the graphitization temperature and graphitizing for 2.5 to 3.5 hours.

[0021] In the preferred technical solution of the method for preparing graphite from peat, the heating rates in the first stage and the second stage are both 5-15°C / min.

[0022] In the preferred technical solution of the method for preparing graphite from peat, the heating rate is 10°C / min, the holding time is 1 minute, and the graphitization time is 3 hours.

[0023] In the preferred technical solution of the above method for preparing graphite from peat, the selected peat is dried to a constant weight before being graphitized.

[0024] In a second aspect, the present application provides graphite, which is prepared by the above-mentioned method for preparing graphite from peat.

[0025] In the preferred technical solution of the above graphite, the graphite is flake graphite.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] (1) The graphite produced by the present invention is flake graphite, which is a single crystal graphite with a high degree of graphitization and a complete lattice development;

[0028] (2) The raw material peat used in the present invention is cheap and easy to obtain;

[0029] (3) The minimum temperature of the present invention is only 2500°C, which reduces the energy consumption in the graphite production process;

[0030] (4) The present invention makes it possible to prepare graphite by graphitizing peat, overcomes the prejudice of the prior art, and further increases the high added value of peat resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings, in which:

[0032] Figure 1 This is a digital photo of the flake graphite obtained in Example 1;

[0033] Figure 2 This is an electron microscope photograph of the flake graphite obtained in Example 1;

[0034] Figure 3 This is a transmission electron microscope photograph of the flake graphite obtained in Example 1;

[0035] Figure 4 Shown are the XRD diffraction patterns of peat ore and graphitized samples prepared from peat ore at different temperatures. DETAILED DESCRIPTION

[0036] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.

[0037] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0038] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0039] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0040] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0041] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0042] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0043] The experimental methods in the following examples are conventional methods unless otherwise specified, and the materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.

[0044] Based on the prior art pointed out in the background technology, technicians in this field usually do not think of graphitizing peat to prepare graphite to further improve the high added value of peat resources because of the prejudice that peat has an optically isotropic structure that is difficult to graphitize. The present application provides a method for preparing graphite from peat, which overcomes the prejudice of the prior art, prepares graphite, and further improves the high added value of peat resources.

[0045] Specifically, the method for preparing graphite from peat of the present application comprises the following steps:

[0046] S1, screening peat;

[0047] S2. Graphitizing the selected peat to obtain.

[0048] In some embodiments, the graphitization temperature is 2500-2900°C.

[0049] In some embodiments, the graphitization temperature is set to 2500°C, 2600°C, or 2900°C.

[0050] The test shows that when the temperature is below 2000℃, peat does not begin to graphitize, and the product is mainly silicon carbide generated by the reaction of quartz and carbon. As the temperature rises to 2300℃, peat partially graphitizes, but the main product is still silicon carbide. When the temperature rises to 2500℃, peat eventually turns into graphite. In addition, when the temperature is 2500℃, 2600℃ and 2900℃, the products are all crystalline flaky graphite, and there is no obvious difference in the degree of graphitization and crystal quality. Therefore, the graphitization temperature of the present invention is selected to be 2500-2900℃.

[0051] In some embodiments, the graphitization time is 2.5 to 3.5 hours.

[0052] In some preferred embodiments, the graphitization time is 3 hours.

[0053] The test shows that when the graphitization time is 2 hours, the lattice development of the final product is incomplete, the graphitization degree is not high, and the flake diameter is not large; when the time is 4 hours, the graphitization degree and flake diameter have no obvious difference with the heat treatment time, but will increase energy consumption and cost. Therefore, the graphitization time of the present invention is selected to be 2.5 to 3.5 hours, and the graphitization treatment time is kept at 3 hours as the best time.

[0054] In some embodiments, the quartz content of the screened peat is 35-60%.

[0055] During the graphitization process of coal, quartz reacts with carbonaceous substances to form an intermediate product of silicon carbide, which then decomposes to produce graphite. Accordingly, when the quartz content is 30%, some carbon will not react with quartz and cannot be catalyzed by quartz. The final product has a low degree of graphitization and an incomplete three-dimensional graphite structure. When the quartz content is 70%, some quartz will remain and not react with carbon. It will decompose at high temperature to form silicon, resulting in silicon impurities in the final product graphite. Therefore, the quartz content in the peat screened by the present invention is 35-60%.

[0056] Studies have shown that silicon dioxide promotes coal graphitization. The mechanism is as follows: silicon dioxide reacts with carbon in coal at high temperature to generate an intermediate product, silicon carbide. As the temperature rises further, silicon carbide is thermally decomposed to form graphite crystals, thereby increasing the graphitization degree of coal. Peat is the coal with the lowest degree of coalification and the most primitive state of coal. The content of mineral quartz in the peat used in the present invention is very high. Further experiments have been conducted to screen out the appropriate graphitization temperature and time, making it possible to graphitize peat into graphite, overcoming the prejudice of the prior art and further increasing the high added value of peat resources.

[0057] In some embodiments, when performing the graphitization, the following heating procedure is set:

[0058] The graphitization temperature is raised to 2500-2900°C and graphitization is performed for 2.5-3.5 hours.

[0059] In some embodiments, the heating rate is 5-15° C. / min.

[0060] In some embodiments, when performing the graphitization, the following heating procedure is set:

[0061] The first stage: rise to 1000-1400℃ and maintain for 0.5-1.5 hours;

[0062] The second stage: rising to the graphitization temperature and graphitizing for 2.5 to 3.5 hours.

[0063] The experiment shows that the heating procedure has no effect on whether peat can be graphitized to produce flake graphite, as long as it is raised to a certain graphitization temperature and maintained for a certain period of time, it can be achieved. However, the above-mentioned staged heating method heats evenly and has a better effect.

[0064] In some embodiments, the heating rates of the first stage and the second stage are both 5-15° C. / min.

[0065] In some preferred embodiments, the heating rates of the first stage and the second stage are both 5-10° C. / min.

[0066] The test shows that when the final temperature of the heating is guaranteed to be 2600℃ and the holding time is 3h, the heating rate will not have a significant effect on the structure of the final product of peat graphitization. When the heating rate is lower than 10℃ / min, the heating time will be too long, which greatly increases the energy consumption and production cost. When the heating rate is higher than 10℃ / min, the damage to the high-temperature graphitization furnace is greater, and there are safety hazards. The high-temperature graphitization furnace may explode due to the excessively fast heating rate. Therefore, the present invention takes 5-10℃ / min as the preferred embodiment.

[0067] In some embodiments, the heating rate is 10° C. / min, the holding time is 1 hour, and the graphitization time is 3 hours.

[0068] In a preferred embodiment, the graphitization is performed in a high-temperature graphitization furnace.

[0069] In some embodiments, the screened peat is dried to a constant weight before being graphitized.

[0070] In some embodiments, the drying temperature is 95-105°C.

[0071] In some embodiments, the drying temperature is set at 100°C, 95°C, or 105°C.

[0072] In some embodiments, the drying is performed in an oven.

[0073] The present application also provides graphite, which is prepared by the above method.

[0074] As a preferred embodiment, the graphite is flake graphite.

[0075] In some embodiments, the flake graphite is single crystal graphite and has a size of up to 2 to 3 mm.

[0076] The properties of the flake graphite obtained by the method for preparing flake graphite from peat at high temperature of the present application are described in detail below through several specific examples of preparing flake graphite from peat at high temperature.

[0077] In the following embodiments, the high-temperature graphitization furnace adopts the Hunan Zhuzhou Enrui JR-SML20 / 30 small high-temperature graphitization furnace; the X-ray diffraction test is completed by using the Dmax-2500PC fully automatic powder X-ray diffractometer of Japan Rigaku; and the morphology of the mineral is observed by using the Japan Hitachi SU8020 field emission scanning electron microscope.

[0078] Example 1

[0079] S1. Select peat with a quartz content of 40% as raw material, place it in an oven, set the oven temperature to 100°C, and dry it to constant weight;

[0080] S2. Put the dried peat into a high-temperature graphitization furnace, set a heating program to graphitize the peat, and obtain flake graphite; the heating program is:

[0081] Stage 1: Heating at a rate of 10°C / min to 1200°C and maintaining for 1 minute;

[0082] The second stage: heating to the graphitization temperature at the same heating rate and graphitizing for 3 hours; the graphitization temperature is 2600°C.

[0083] The structure and morphology of the prepared flake graphite are analyzed as follows:

[0084] Figure 1 This is a digital picture of the prepared flake graphite. From the picture, it can be observed that the graphite presents an obvious hexagonal flake structure with a size ranging from 2 to 3 mm.

[0085] Figure 2 is a scanning electron microscope image of the prepared flake graphite, wherein: Figure 2 a is a scanning electron microscope picture, from which it can be clearly seen that the product is flaky graphite with a large grain size. The layered stacking structure of graphite can be seen at the edge, and the crystal has no obvious defects, forming a relatively ideal graphite crystal. Figure 2 b is a side scanning electron microscope image, from which the layered stacking structure can be clearly observed. At the same time, the number of graphite wafers is large and arranged regularly.

[0086] Figure 3 The transmission electron microscope image of the prepared flake graphite is shown in Figure 1. Figure 3 a and Figure 3 b The nanoscale reveals that the flake graphite has a highly ordered graphite structure, with aromatic sheets arranged very regularly and without obvious pores and defects.

[0087] The preparation methods of graphite in Examples 2 to 8 are the same as those in Example 1, the only difference being that the process parameters of each step are different, as specifically shown in Table 1.

[0088] Table 1. Related parameters of each step in Example 2 to Example 8

[0089] Test Example 1

[0090] This experiment investigated the product characteristics of peat at different heat treatment temperatures. The peat was heated to 2000℃, 2300℃, 2500℃, 2600℃ and 2900℃ respectively. The effect of different temperatures on the graphitization of peat samples was explored.

[0091] 1) Place peat with a quartz content of 40% in an oven and dry until constant weight;

[0092] 2) The dried raw materials were placed in a small high-temperature graphitization furnace of Zhuzhou Enrui JR-SML20 / 30, argon was introduced as a protective gas, and then the target temperatures were set to 2000°C, 2300°C, 2500°C, 2600°C and 2900°C. The temperature was raised to 1200°C at a rate of 10°C / min and maintained for 1 hour, then raised to the target temperature at the same rate of heating, and kept warm for 3 hours, and finally peat samples at various temperatures were obtained.

[0093] The structure and morphology of the peat ore and the graphitized samples prepared at different temperatures of the peat in step 2) were analyzed. The XRD comparative analysis results are as follows: Figure 4 As shown. Among them:

[0094] Figure 4 a is the XRD diffraction pattern of unheated peat ore. Figure 4 It can be seen from a that the main mineral in peat is quartz, with a bulge peak at around 22° (2θ) and no obvious crystal diffraction peak, that is, an irregular network structure composed of silicon-oxygen tetrahedrons. After heating to 2300°C by the above method, the XRD curve begins to show an obvious (002) diffraction peak, indicating that peat begins to graphitize. At 2600°C, the (004) and (002) diffraction peaks become sharp ( Figure 4 b), indicating that the peat has been completely graphitized.

[0095] Figure 4 b is the XRD diffraction pattern of graphitized samples of peat ore prepared at different temperatures. Figure 4b It can be seen that the product at each temperature has a diffraction peak at ~26° (2θ), which is the (002) diffraction peak of coal / graphite. At 2000℃, the (002) diffraction peak is not obvious, indicating that the sample has not started to graphitize at this time, and the product is mainly silicon carbide generated by the reaction of quartz and carbon. As the temperature rises to 2300℃, the peak intensity of the (002) diffraction peak begins to become stronger and shifts to a higher angle, reflecting that peat is partially graphitized at this temperature, and the main product at this temperature is still silicon carbide. When the temperature rises to 2500℃, the characteristic peak of silicon carbide disappears, decomposing into elemental silicon and graphite, and obvious graphite (002) peak and (004) peak appear, but this peak is a double peak. The reason is that as the crystal quality of graphite crystals improves, not only the XRD ray diffraction peak of Kα1, but also the diffraction peak of Kα2 is shown, so two adjacent peaks appear. In addition, the three-dimensional characteristic diffraction peaks of graphite appeared at 42.34°, 44.5° and 54.66°, respectively, indicating that peat eventually turned into graphite. In addition, at temperatures of 2500°C, 2600°C and 2900°C, the products were all crystalline flaky graphite, and there was no significant difference in the degree of graphitization and crystal quality.

[0096] Test Example 2

[0097] This test example investigated whether flake graphite can be produced from peat without drying it before graphitization.

[0098] Experimental methods:

[0099] Select peat with quartz content of 40% as raw material, put it into a high-temperature graphitization furnace, and set the following heating program:

[0100] Stage 1: Heating at a rate of 10°C / min to 1200°C and maintaining for 1 minute;

[0101] The second stage: heat up to 2600℃ at the same heating rate and keep warm for 3 hours.

[0102] The structural and morphological analysis of the obtained samples showed that flake graphite can be produced from peat without drying.

[0103] The above test results show that what peat loses during the drying process is the mobile water inside, usually called free water. Drying has no effect on the properties of the substance itself, so flake graphite can be produced from peat without drying.

[0104] Test Example 3

[0105] This test example investigated the effect of graphitization time on whether flake graphite can be produced.

[0106] Test method:

[0107] Refer to Example 1, except that the graphitization time is 2h, 3h and 4h respectively.

[0108] The results show that when the graphitization time is 2 hours, the lattice development of the final product is incomplete, the graphitization degree is not high, and the flake diameter is not large; when the time is 4 hours, the graphitization degree and flake diameter have no significant difference with the heat treatment time, but will increase energy consumption and cost. Therefore, the graphitization treatment time is kept at 3 hours, which is the best time.

[0109] Test Example 4

[0110] This test example investigated the effect of the quartz content in peat on whether flake graphite can be produced.

[0111] Test method:

[0112] Refer to Example 1, except that the quartz contents in the selected peat are 30%, 35%, 40%, 50%, 60% and 70% respectively.

[0113] The results show that during the graphitization of coal, quartz reacts with carbonaceous substances to form an intermediate product of silicon carbide, which then decomposes to produce graphite. Based on this, when the quartz content is 30%, some carbon will not react with quartz and cannot be catalyzed by quartz. The final product has a low degree of graphitization and an incomplete three-dimensional graphite structure. When the quartz content is 70%, some quartz will remain and not react with carbon. It will decompose at high temperature to form silicon, resulting in silicon impurities in the final product graphite. When the quartz content is 35-60%, peat can be completely graphitized.

[0114] Test Example 5

[0115] This test example investigated the effect of the heating procedure on whether flake graphite can be produced.

[0116] Test method:

[0117] With reference to Example 1, the difference is that the heating program adopted is:

[0118] The temperature was raised to 2600°C at a heating rate of 10°C / min and kept at this temperature for 3 hours.

[0119] The results show that the final product is flake graphite with a high degree of graphitization, no obvious defects in the lattice, and a well-developed three-dimensional structure. That is, the purpose of graphitization can be achieved by raising the temperature to the graphitization temperature once and keeping it at the graphitization temperature for a certain period of time.

[0120] Test Example 6

[0121] This test example investigates the effect of heating rate on the prepared flake graphite.

[0122] Test method:

[0123] Refer to Example 1, except that the heating rates used are 1°C / min, 3°C / min, 10°C / min, and 16°C / min, respectively.

[0124] The results show that when the final heating temperature is guaranteed to be 2600℃ and the insulation time is 3h, the heating rate will not have a significant effect on the structure of the final product of peat graphitization. When the heating rate is lower than 10℃ / min, the heating time will be too long, which greatly increases the energy consumption and production costs. When the heating rate is greater than 10℃ / min, the damage to the high-temperature graphitization furnace is greater and there are safety hazards. The high-temperature graphitization furnace may explode due to the excessively fast heating rate.

[0125] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.

Claims

1. A method for preparing graphite from peat, characterized in that: include: sifting peat; The selected peat is graphitized to obtain the product.

2. The method according to claim 1, characterized in that The graphitization temperature is 2500-2900°C.

3. The method according to claim 2, characterized in that The graphitization time is 2.5 to 3.5 hours, preferably 3 hours.

4. The method according to any one of claims 1 to 3, characterized in that: The quartz content in the screened peat is 35-60%.

5. The method according to claim 4, characterized in that When performing the graphitization, the following heating program is set: Raise the graphitization temperature to 2500-2900°C and graphitize for 2.5-3.5 hours; Preferably, the following heating program is set: The first stage: rise to 1000-1400℃ and maintain for 0.5-1.5 minutes; The second stage: rising to the graphitization temperature and graphitizing for 2.5 to 3.5 hours.

6. The method according to claim 5, characterized in that The heating rates in the first and second stages are both 5-15°C / min.

7. The method according to claim 5, characterized in that The heating rate is 10°C / min, the first stage maintenance time is 1 hour, and the graphitization time is 3 hours after reaching the graphitization temperature.

8. The method according to claim 5, characterized in that The screened peat was dried to constant weight before graphitization.

9. A graphite, characterized in that: The graphite is prepared by the method according to any one of claims 1 to 8.

10. The graphite according to claim 9, characterized in that The graphite is flaky graphite.

Citation Information

Patent Citations

  • Photocatalytic active carbon aerogel material and preparation method thereof

    CN112517069A

  • Sodium ion battery negative electrode material and preparation method thereof

    CN118343749A